Effects of intervention focused on eating behavior and dietary prescription in patients with Type 1 Diabetes: a pilot study (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
The objective was to compare the effects of interventions, based on mindfulness plus culinary workshops, and dietary prescription, on the level of mindfulness and macronutrient intake of adults with Type 1 Diabetes. After screening, 5 subjects were randomized (P1 to P5) in Control Group, Intervention 1 and 2. In Intervention Group 1, the Healthy Eating Workshop and dietary prescription were realized. In Intervention Group 2, Healthy Eating Workshops, Workshops with Techniques based on mindfulness and three Culinary Workshops were realized. There was low adherence to fruit intake and dietary prescription (P2 = 44.45%; P3 = 8.33%). Comparing weeks 1 and 11, the mindfulness score increased in the Intervention 2 Group and decreased in the other groups. Mindfulness-based techniques and united culinary workshops had a interesting results on the level of mindfulness and the reframing of foods that generate guilt.
Keywords: Type 1 Diabetes Mellitus; Cooking; Diet; Mindfulness